Novel phthalazinone‐bearing tetrafunctional epoxy: Synthesis, characterization, and their toughening application for TGDDM system. (6th February 2020) - Zhang, Fengfeng; Zong, Lishuai; Bao, Feng; Weng, Zhihuan; Wang, Chenghao; Wang, Jinyan; Jian, Xigao
Abstract : A novel tetrafunctional epoxy (TEPZ) was synthesized by "one spot two steps" method, and the effects of solvents, reaction temperature, and mole ratios of reactants on the reaction conversion were systematically investigated. The results demonstrated that the solvents participating in the reaction were the most crucial factor for high conversions. After curing, TEPZ/4, 4′‐diaminodiphenyl sulfone (DDS) system exhibited better thermal stability compared with famous N, N, N′, N′‐tetraglycidyl‐4, 4′‐diaminodiphenyl methane (TGDDM)/DDS analog. When TEPZ is blended with TGDDM/DDS, the initial decomposition temperature of TGDDM/TEPZ/DDS hybrid elevated from 348°C to 362°C. The storage modulus and the glass transition temperature were sensitive to curing procedure and concentration of DDS. While the system consisted of 100 phr TGDDM, 30 phr TEPZ, and 40 phr DDS, the storage modulus and glass transition temperature increased significantly compared with those of TGDDM/DDS, and the impact strength increased by 31.6% simultaneously. Such enhancement could be ascribed to the structural feature of phthalazinone in TEPZ, which formed stable interpenetrating networks during thermal cure procedure.